1971
DOI: 10.1063/1.1685351
|View full text |Cite
|
Sign up to set email alerts
|

Time Domain Compensation of Cable Induced Distortions Using Passive Filters for the Transmission of Fast Pulses

Abstract: Passive sonar classification using timefrequency domain "features".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Z a and Z b are complex impedances such that Z a Z b = R 2 . The frequency response of the networks is then Examples of other applications are described in §4.3.2 and in [16].…”
Section: Constant Resistance T and L Networkmentioning
confidence: 99%
“…Z a and Z b are complex impedances such that Z a Z b = R 2 . The frequency response of the networks is then Examples of other applications are described in §4.3.2 and in [16].…”
Section: Constant Resistance T and L Networkmentioning
confidence: 99%
“…Fortunately, it has been demonstrated that for a typical LHC transmission rate of 40 Mbit/s, transmission distortions can be successfully compensated with passive filters known as impedance equalisers [2]. It was found that signal transmission based on the LVDS provides a good signal integrity over distances of 100 metres and above, using passive filters [3][4][5]. Despite these promising results, a more systematic test was needed to verify the quality of signal transmission for ALICE applications.…”
Section: Motivationmentioning
confidence: 99%